2010
DOI: 10.1186/2041-9139-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Conserved developmental expression of Fezf in chordates and Drosophila and the origin of the Zona Limitans Intrathalamica (ZLI) brain organizer

Abstract: BackgroundThe zona limitans intrathalamica (ZLI) and the isthmus organizer (IsO) are two major secondary organizers of vertebrate brain development. These organizers are located at the interface of the expression domains of key patterning genes (Fezf-Irx and Otx-Gbx, respectively). To gain insights into the evolutionary origin of the ZLI, we studied Fezf in bilaterians.ResultsIn this paper, we identified a conserved sequence motif (Fezf box) in all bilaterians. We report the expression pattern of Fezf in amphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 57 publications
3
50
0
Order By: Relevance
“…6). This gene is involved in establishing a deeply conserved early anterior-posterior (A-P) brain patterning (Simeone et al 1992;Hirth et al 2003;Castro et al 2006;Irimia et al 2010) and is expressed in the anterior nervous system of nearly all studied bilaterians (Simeone et al 1992;Williams and Holland 1996;Hirth et al 2003;Lowe et al 2003;Scholpp et al 2007). We found that Otx is linked to Ehbp1 (EH domain binding protein 1) in nearly all species, from placozoans to humans, spanning over 700 MY (Fig.…”
Section: Experimental Evidence For Grbs In Vertebrate Developmentmentioning
confidence: 99%
“…6). This gene is involved in establishing a deeply conserved early anterior-posterior (A-P) brain patterning (Simeone et al 1992;Hirth et al 2003;Castro et al 2006;Irimia et al 2010) and is expressed in the anterior nervous system of nearly all studied bilaterians (Simeone et al 1992;Williams and Holland 1996;Hirth et al 2003;Lowe et al 2003;Scholpp et al 2007). We found that Otx is linked to Ehbp1 (EH domain binding protein 1) in nearly all species, from placozoans to humans, spanning over 700 MY (Fig.…”
Section: Experimental Evidence For Grbs In Vertebrate Developmentmentioning
confidence: 99%
“…In vertebrates, Otx and Gbx mutually repress one another and have been shown to position the MHB; they likely do so as well in amphioxus. Similarly, in vertebrates, the domains of Fezf and Irx, which mutually repress each other, abut at the ISO and in amphioxus abut about the midpoint of the diencephalon (Irimia et al, 2010). In S. kowalevskii, Otx, Gbx, Fezf and Irx are not expressed as they are in chordates (Pani et al, 2012) (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…These data have been used to support the plausible hypothesis that most vertebrate brain signaling centers were sequentially assembled during chordate evolution. In this scenario, the recruitment of signaling ligands to these centers was the final step achieved in stem vertebrates (Holland, 2009;Irimia et al, 2010). However, ectodermal signaling centers that might be homologous to three of those found in vertebrate brains have now been described in S. kowalevskii (Pani et al, 2012), suggesting that these developmental programs predate chordate origins and were first assembled independently of the vertebrate brain.…”
Section: Basic Body Plan Comparisons Anteroposterior Patterningmentioning
confidence: 99%
“…In all vertebrates, local signaling centers in the neural plate, characterized by expression of secreted ligands in predictable AP positions within a conserved transcriptional map, act to divide the brain into discrete regions (Wurst and Bally-Cuif, 2001;Echevarria et al, 2003;Wilson and Houart, 2004;Kiecker and Lumsden, 2005). Although some of the transcriptional signatures associated with vertebrate signaling centers are present in invertebrate chordates (Holland, 2009;Irimia et al, 2010), in most instances the signaling ligands that define the organizing abilities of these centers in vertebrates are not expressed in the corresponding AP positions in the amphioxus and ascidian nervous systems or general ectoderm. These data have been used to support the plausible hypothesis that most vertebrate brain signaling centers were sequentially assembled during chordate evolution.…”
Section: Basic Body Plan Comparisons Anteroposterior Patterningmentioning
confidence: 99%